2019
DOI: 10.3390/ani9050261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfur Levels in Fermented Total Mixed Ration Containing Fresh Cassava Root on Feed Utilization, Rumen Characteristics, Microbial Protein Synthesis, and Blood Metabolites in Thai Native Beef Cattle

Abstract: The influence of sulfur included in fermented total mixed ration (FTMR) containing fresh cassava root on rumen characteristics, microbial protein synthesis, and blood metabolites in cattle was evaluated. Four Thai native beef cattle were randomly assigned according to a 2 × 2 factorial in a 4 × 4 Latin square design, and dietary treatments were as follows: factor A included a level of sulfur at 1% and 2% in total mixed ration, and factor B featured ensiling times at zero and 7 days. Digestibility of dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 26 publications
7
57
2
Order By: Relevance
“…Laminarase enzymes can break down activity at a lower pH to degrade linamarine to HCN, thereby reducing toxic effects [28]. In agreement with the present study, Supapong et al [12] found that beef cattle fed a diet containing 1.0% to 2.0% sulfur experienced reduced HCN concentrations by 99.3% to 99.5%.…”
Section: Chemical Contents In the Dietssupporting
confidence: 90%
See 2 more Smart Citations
“…Laminarase enzymes can break down activity at a lower pH to degrade linamarine to HCN, thereby reducing toxic effects [28]. In agreement with the present study, Supapong et al [12] found that beef cattle fed a diet containing 1.0% to 2.0% sulfur experienced reduced HCN concentrations by 99.3% to 99.5%.…”
Section: Chemical Contents In the Dietssupporting
confidence: 90%
“…Furthermore, Cherdthong et al [2] found that cattle consuming fresh cassava root in the basal diet with feed block at 4.0% sulfur levels showed improved DM and OM digestibility by 13.0% and 12.1%, respectively. An earlier report by Supapong et al [12], showed that beef cattle fed a diet supplemented with 2.0% sulfur in the FTMR exhibited increased DM digestibility by 4.2% compared to those fed with a diet supplemented with 1.0% sulfur.…”
Section: Nutrient Intake and Digestibilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Concentrations of NH3-N were significantly impacted (p < 0.05) and decreased with increased rates of FCR supplementation. This could be due to a sufficient supply of energy from a rapidly fermentable source of carbohydrates to allow the efficient incorporation of peptides, free amino acids, and NH3-N into microbial cells [10]. Likewise, Cherdthong et al [2] found that the concentration of NH3-N in the rumen increased with an increasing amount of FCR supplementation.…”
Section: In Vitro Fermentation and Ruminal Microbial Populationmentioning
confidence: 99%
“…Cherdthong et al [2] found that supplementation of FCR at 10 g/kg and 15 g/kg of BW with feed blocks containing sulfur at 20 and 40 g/kg did not have a negative effect on digestibility and rumen fermentation, and cyanide from FCR can be changed to thiocyanate, which is less toxic to animals. Additionally, Supapong et al [10] suggested that 20 g sulfur/kg supplementation in fermented total mixed ration (FTMR) containing FCR and fermented for 7 days improved digestibility of nutrients, microbial protein synthesis effectiveness, and total volatile fatty acids (VFAs), propionic acid, and thiocyanate in blood. However, feeding animals with feed products such as sulfur-containing pellets requires, in particular, an increase in value-added feed and a convenient practical use for farmers.…”
Section: Introductionmentioning
confidence: 99%